KAJIAN TENTANG FUNGSI SISTEM INFORMASI PERENCANAAN PEMBANGUNAN DAERAH (SIPPD) DALAM PROSES PERENCANAAN PEMBANGUNAN DI KABUPATEN POSO - Jamal, Agung Laksana (Katalogis, 2016)
This study aims at determiningthe differencesbefore and after use of Information System for Regional Development in the process of development planning in Poso district. This is a descriptive, qualitative and quantitative research with 43 (forty-three) people as the total number of population, and the total sample is 43 people selected by using census sampling technique. The data were collected through questionnaires and interview guidelines. The analysis of the data is descriptive quantitative and qualitative. The indicators used are the number of proposals that followed, the percentage of the consistency of the planned programs and activities and percentage of evaluated program and activities. The results show that there were significant differences after the use of SIPPD. ThisÂ  is shown by the results of difference test with t value of each indicator is the number of followed proposals 3.954, consistency percentage of planned programs and activities is 12 610, the percentage of evaluated programs and activities is 17 048 greaterthan the t table value 2.018. The study also suggests that it is needed to develop a system that suits the needs so that it can facilitate the preparation of impotant documents and development plans for each agency allocating a budget for increasing the capacity of SIPPD admin and providing cost consequences as motivation in the work.